Adipose triglyceride lipase gene expression in peripheral blood mononuclear cells of subjects with obesity and its association with insulin resistance, inflammation and lipid accumulation in liver - Samira Ezzati‐Mobaser; Sahar Yarahmadi; Nikta Dadkhah Nikroo; Mohammad Hasan Maleki; Zeynab Yousefi; Pegah Golpour; Mona Nourbakhsh; Mitra Nourbakhsh (Wiley, 2024)
Abstract Introduction Adipose triglyceride lipase (ATGL) is a crucial enzyme responsible for the release of fatty acids from various tissues. The expression of ATGL is regulated by insulin and this enzyme is linked to Insulin resistance (IR). On the other hand, ATGL‐mediated lipolysis is connected to macrophage function and thus, ATGL is involved in inflammation and the pathogenesis of lipid‐related disorders. This study aimed to investigate the correlation between ATGL, obesity, Metabolic Syndrome (MetS), and inflammation. Methods A total of 100 participants, including 50 individuals with obesity and 50 healthy participants, were recruited for this study and underwent comprehensive clinical evaluations. Blood samples were collected to measure plasma lipid profiles, glycemic indices, and liver function tests. Additionally, peripheral blood mononuclear cells (PBMCs) were isolated and used for the assessment of the gene expression of ATGL, using real‐time PCR. Furthermore, PBMCs were cultured and exposed to lipopolysaccharides (LPS) with simultaneous ATGL inhibition, and the gene expression of inflammatory cytokines, along with the secretion of prostaglandin E2 (PGE2), were measured. Results The gene expression of ATGL was significantly elevated in PBMCs obtained from participants with obesity and was particularly higher in those diagnosed with MetS. It exhibited a correlation with insulin levels and Homeostatic Model Assessment for IR (HOMA‐IR), and it was associated with lipid accumulation in the liver. Stimulation with LPS increased ATGL expression in PBMCs, while inhibition of ATGL attenuated the inflammatory responses induced by LPS. Conclusions Obesity and MetS were associated with dysregulation of ATGL. ATGL might play a role in the upregulation of inflammatory cytokines and act as a significant contributor to the development of metabolic abnormalities related to obesity.